Chemical State Information of Bulk Specimens Obtained by SEM-Based Soft-X-Ray Emission Spectrometry. (14th March 2014) - Terauchi, Masami; Koshiya, Shogo; Satoh, Futami; Takahashi, Hideyuki; Handa, Nobuo; Murano, Takanori; Koike, Masato; Imazono, Takashi; Koeda, Masaru; Nagano, Tetsuya; Sasai, Hiroyuki; Oue, Yuki; et al.
Abstract Electron-beam-induced soft-X-ray emission spectroscopy (SXES) that uses a grating spectrometer has been introduced to a conventional scanning electron microscope (SEM) for characterizing desired specimen areas of bulk materials. The spectrometer was designed as a grazing incidence flat-field optics by using aberration corrected (varied line spacing) gratings and a multichannel plate detector combined with a charge-coupled device camera, which has already been applied to a transmission electron microscope. The best resolution was confirmed as 0.13 eV at Mg L-emission (50 eV), which is comparable with that of recent dedicated electron energy-loss spectroscopy instruments. This SXES-SEM instrument presents density of states of simple metals of bulk Mg and Li. Apparent band-structure effects have been observed in Si L-emission of Si wafer, P L-emission of GaP wafer, and Al L-emissions of intermetallic compounds of AlCo, AlPd, Al2Pt, and Al2Au.